Development of an Android Application for Monitoring the SMART Aquaponics System for Cultivating Catfish and Water Spinach Plants - Viving Frendiana; Morrin Nadya Pangesti (Politeknik Negeri Jakarta, 2025)
Aquaponics is a combination of aquaculture systems in the form of fish and hydroponic cultivation in the form of plants. Catfish growth will be optimal in water conditions with a temperature of 26°C - 30°C and a water pH of 6 - 9. Therefore, monitoring aquaponic water quality is needed to improve fish and plant growth. To facilitate the monitoring of water quality and plant growth, an Android-based mobile application